Enzymatic Active Release of Violacein Present in Nanostructured Lipid Carrier by Lipase Encapsulated in 3D-Bioprinted Chitosan-Hydroxypropyl Methylcellulose Matrix With Anticancer Activity - Rivero Berti, Ignacio; Rodenak-Kladniew, Boris E.; Katz, Sergio F.; Arrua, Eva Carolina; Alvarez, Vera A.; Duran, Nelson; Castro, Guillermo R. (Frontiers in Chemistry, 2022)
Violacein (Viol) is a bacterial purple water-insoluble pigment synthesized by Chromobacterium violaceum and other microorganisms that display many beneficial therapeutic properties including anticancer activity. Viol was produced, purified in our laboratory, and encapsulated in a nanostructured lipid carrier (NLC). The NLC is composed of the solid lipid myristyl myristate, an oily lipid mixture composed of capric and caprylic acids, and the surfactant poloxamer P188. Dormant lipase from Rhizomucor miehei was incorporated into the NLC-Viol to develop an active release system. The NLC particle size determined by dynamic light scattering brings around 150 nm particle size and ζ≈ −9.0 mV with or without lipase, but the incorporation of lipase increase the PdI from 0.241 to 0.319 (≈32%). For scaffold development, a 2.5 hydroxypropyl methylcellulose/chitosan ratio was obtained after optimization of a composite for extrusion in a 3D-bioprinter developed and constructed in our laboratory. Final Viol encapsulation efficiency in the printings was over 90%. Kinetic release of the biodye at pH = 7.4 from the mesh containing NLC-lipase showed roughly 20% Viol fast release than without the enzyme. However, both Viol kinetic releases displayed similar profiles at pH = 5.0, where the lipase is inactive. The kinetic release of Viol from the NLC-matrices was modeled and the best correlation was found with the Korsmeyer-Peppas model (R2 = 0.95) with n < 0.5 suggesting a Fickian release of Viol from the matrices. Scanning Electron Microscope (SEM) images of the NLC-meshes showed significant differences before and after Viol’s release. Also, the presence of lipase dramatically increased the gaps in the interchain mesh. XRD and Fourier Transform Infrared (FTIR) analyses of the NLC-meshes showed a decrease in the crystalline structure of the composites with the incorporation of the NLC, and the decrease of myristyl myristate in the mesh can be attributed to the lipase activity. TGA profiles of the NLC-meshes showed high thermal stability than the individual components. Cytotoxic studies in A549 and HCT-116 cancer cell lines revealed high anticancer activity of the matrix mediated by mucoadhesive chitosan, plus the biological synergistic activities of violacein and lipase.